The Links Between Financial Education and Financial Literacy - Szőke, Brigitta; Tóth, Eszter (Acta Carolus Robertus, 2023)
The aim of this research is to examine the relationship between financial education and financial literacy. A key area today is the conscious management of our personal finances; in fact, every decision we make has a financial dimension that affects our short and/or long term financial management. Despite the interest of all stakeholders in improving financial literacy, progress is still very slow. Unfortunately, financial education is slow to pay back the time and energy invested in the long term. In many cases, short-term interests and present problems override long-term goals, and many people remain indifferent to their finances and do not look beyond 1-2 years. The rapid pace of change in the world means that many people are distrustful of the future and do not plan ahead consciously. In primary, secondary and higher education, we need to move forward in teaching financial and economic education, so educational institutions will have a very big responsibility to ensure that the future generation makes informed choices about their finances.
Keywords: education; financial awareness; financial culture; financial literacy; extra-curricular activities